FRI0746 Nursing consultation versus rheumatologist follow up for patients with stable rheumatoid arthritis: a randomized controlled trial. (12th June 2018) - Kwok, G.S.K.; Cheung, T.T.; Tang, M.L.M.; Yuen, C.K.Y.; Chung, H.Y.; Lau, W.C.S.
Abstract : Background: Conventionally, patients with RA have been managed by scheduled routine consultations by rheumatologists every 3 to 6 months. However, the burden of RA has been increasing globally. Altough rheumatology nursing consultation was shown to be an effectiveness management strategy in western countries, its feasibility has not been evaluated in Chinese population. Therefore, we would like to compare the efficacy of rheumatology nursing consultation with usual rheumatologist follow-up in Hong Kong. Objectives: To evaluate the efficacy of rheumatology nursing consultation in patients with stable RA over 1 year. Methods: Study design and patient selection: This is a single centre, randomized controlled, non-inferiority trial conducted in Queen Mary Hospital. Patients with RA were recruited from the rheumatology clinic in Queen Mary Hospital. Subjects have to fulfill the 2010 ACR-EULAR classification criteria for RA, with DAS28-CRP≤3.2 for at least 6 months with no increase in dose of conventional synthetic disease modifying anti-rheumatic drugs (csDMARDs). Subjects with systemic manifestation of RA, current malignancies or current use of biologic therapies were excluded. Intervention: Subjects were randomized in a 1:1 ratio to the following treatment groups. Usual rheumatologist follow-up (control): Subjects were followed up by rheumatologists or registrars every 4 months. The treatment target was to maintain the DAS28-CRP≤3.2. Rheumatology nursing consultation: Subjects were followed up by the rheumatology nurses every 4 months. At 12 months, all subjects will be reviewed by a senior rheumatologist. The treatment target was to maintain the DAS28-CRP≤3.2. Outcomes: The primary outcome was the difference in proportion of subjects who remained to have DAS28-CRP≤3.2 at 12 months. Secondary outcomes included the difference in proportion of subjects with DAS28-CRP>0.6 at 12 months; the change in modified Sharp score, health assessment questionnaire (HAQ) score, patients' drug compliance from baseline and patients' satisfaction at 12 months. Statistical analysis: SPSS v.22 was used to performed the statistical analyses according to intention to treat and per protocol analysis. The comparisons between 2 groups was performed by Student's t-test for continuous variables and chi-square test for categorical variables. A one-way repeated measures ANOVA was conducted to determine if there was a difference in DAS28-CRP between treatment groups during the study period. Results: 276 subjects were randomized to receive rheumatology nurse consultation or usual rheumatologist follow-up. At 12 months, 95.5% and 90.5% of subjects in the nurse consultaton and rheumatologist follow-up remained to have low disease activity respectively, with an adjusted treatement difference of 5.0% (CI -1.27–11.54) and showed non-inferiority with a pre-defined margin of -10%. However, more subjects in the rheumatologist follow-up experienced DAS28-CRP>0.6 at 12 months. One-way repeated measures ANOVA test showed significant difference in DAS28-CRP between 2 treatement group over time. No statistically significant differences were seen in other outcome measures. Conclusions: Rheumatology nurse consultation is not inferior to regular rheumatologist follow-up for rheumatoid arthritis patients with low disease activity. Disclosure of Interest: None declared